Women`s awareness raising in the development of ecotourism: Evidence from Glugut Park Yogyakarta, Indonesia - Tohani, Entoh (Publisher of Widyagama University of Malang (UWG Press), 2022)
Awareness is a driving force for women to be involved in ecotourism management. With objective awareness, they will become tourism actors who can play an active and productive role in providing tourism services to visitors. This study aims to determine the rise of awareness in the development of ecotourism. Women's awareness in ecotourism management needs to be developed in order to ensure the existence of tourism to be more useful and they can participate actively in tourism management. This research used a qualitative approach. The subjects of this research were the manager coordinator, tourism manager, members of Dasawisma, and the local community in the Glugut Park Tourism, in Bantul, Indonesia. Their participation was decided by purposive sampling. Data collection techniques used were observation, interviews, and documentation. The data validity was done by triangulating the source and extended observation. The results show that increasing women's awareness can eventuate and be impactful toward their active participation in the tourism management. Therefore, for optimal result, women’s capacity improvement in regard to local-potential-based tourism development needs to be fully worked on so that they will get additional meaningful effects.JEL Classification: I29; O10; Z32